Do Sharia-Indexed Firms Enhance ESG Disclosure? Evidence from Indonesian Mining - Salisa, Meilenia Rahma; Isa, Yudisthira Jannata Muhammad (LifeSciFi, 2025)
This study explores the influence of asset retirement obligations and firm size on environmental, social, and governance disclosure, with Sharia index inclusion as a moderating factor among mining companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The aim is to assess how environmental liabilities and organizational resources affect environmental, social, and governance disclosure and whether Sharia compliance modifies these relationships, contributing to ESG and Islamic finance literature. The research analyzes panel data from mining firms using moderated regression to evaluate the impact of asset retirement obligations, firm size, and Sharia index inclusion on environmental, social, and governance disclosure. Findings show that of asset retirement obligations and firm size positively influence ESG disclosure, driven by transparency needs and resource availability. However, Sharia index inclusion does not strengthen the asset retirement obligations environmental, social, and governance link, as firms view reclamation as a financial burden rather than a sustainability commitment. Conversely, it enhances the firm size-environmental, social, and governance relationship, reflecting higher stakeholder expectations for Sharia-compliant firms. The study highlights of asset retirement obligations and firm size as key drivers of ESG disclosure, with Sharia compliance amplifying the size effect but not environmental commitments. It offers practical insights for regulators, investors, and managers to foster sustainable governance in resource-intensive sectors.